Interactive H5P Framework-Based E-Learning Content in Artificial Intelligence Lectures of Indonesian Language and Literature - Muhammad Anggie Januarsyah Daulay; Achmad Yuhdi; Adek Cerah Kurnia Azis (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop interactive e-learning content based on the H5P framework in Indonesian Language and Literature Artificial Intelligence lectures at the Indonesian Literature Study Program, Faculty of Languages and Arts, Universitas Negeri Medan with the formulation of the problem of how the content development takes place and how the content is feasible. Methodology: This study uses the Research and Development method with the ADDIE model research procedure (Analysis, Design, Development, Implementation, and Evaluation). Main Findings: E-learning based on the H5P framework in Indonesian Language and Literature Artificial Intelligence lectures is very effective. Validation by media experts showed a very good assessment (89.58% for episode 1 and 97.91% for episode 2). Validation by material experts also showed similar results (93.18% for episode 1 and 97.72% for episode 2). The interactive content developed in the form of video podcasts was able to improve student understanding and engagement through interactive quizzes and simulations. Novelty/Originality of this study: This study develops interactive learning content based on H5P in a new context, namely the Artificial Intelligence course for Indonesian Language and Literature.